Dance in the faith life of the contemporary filipino catholic - Manalo, Ma. Corazon (Animo Repository, 1994)
This is a descriptive phenomenological study that to situates dance in the faith life of the contemporary Filipino Catholic. This research also documents selected dance-laced religious celebrations among lowland Filipino Christians vis-a-vis some dance ethnic non-Christian religious rituals.The data were taken from (1) ethnographic exposures (2) indigenous documentary and library research, (3) the people's experience of religious dance in selected places, (4) various interviews and interactions with dance exponents and enthusiasts. Some persons involved in dance research, culture, arts and related sciences, and church liturgy were also considered as resource persons.The study covered a wide range of Philippine dances. In this study, only the religious dances were studied in depth. From among the data collected, the Dances of Homo Religiosus were classified according to Guzie's level of religion/religious development. These levels were systematic control, idealization, and personal processes. Representative dance religious rituals were annotated according to Francisca Reyes Aquino's classic/standard format in dance notation.Forty-two (42) Philippine traditional dances and eight (8) religious celebrations were considered as Dances of Homo Religiosus. Through their features and mode of expression, the Dances of Homo Religiosus were primarily idealization dances with some traces of the systemic control characteristics. The dances had some touches of personal process elements. Two dances remained on the systemic control level. This phenomenon was attributed to the Filipino historic-cultural and religious foundation. The Dances of Homo Religiosus powerfully speak as symbols of faith.While a combination of folk religiosity and formalized/official Catholicism exists in the Dances of Homo Religiosus, Filipino religiosity is a result of two faith expressions--Eastern and Western. This fusion of seemingly disparate culture seemingly brings about a rich array of religious ritual dances which are considerably Filipino, but no less Christian.